Interrater and Intrarater Reliability of Cranial Anthropometric Measurements in Infants with Positional Plagiocephaly - Iñaki Pastor-Pons; María Orosia Lucha-López; Marta Barrau-Lalmolda; Iñaki Rodes-Pastor; Ángel Luis Rodríguez-Fernández; César Hidalgo-García; Jose Miguel Tricás-Moreno (MDPI AG, 2020)
(1) Background: anthropometric measurements with calipers are used to objectify cranial asymmetry in positional plagiocephaly but there is controversy regarding the reliability of different methodologies. Purpose: to analyze the interrater and intrarater reliability of direct anthropometric measurements with caliper on defined craniofacial references in infants with positional plagiocephaly. (2) Methods: 62 subjects (<28 weeks), with a difference of at least 5 mm between cranial diagonal diameters. Maximal cranial circumference, length and width and diagonal cranial diameters were measured. Intrarater (2 measurements) and interrater (2 raters) reliability was analyzed. (3) Results: intra- and interrater reliability of the maximal cranial length and width and right cranial diagonal was excellent: intraclass correlation coefficient (ICC) > 0.9. Intrarater and interrater reliability for the left cranial diagonal was excellent: ICC > 0.9 and difference in agreement in the Bland-Altman plot 0.0 mm, respectively. Intrarater and interrater reliability for the maximal cranial circumference was good: differences in agreement in Bland-Altman plots: intra: −0.03 cm; inter: −0.12 cm. (4) Conclusions: anthropometric measurements in a sample of infants with moderate positional plagiocephaly have shown excellent intra- and interrater reliability for maximal cranial length, maximal cranial width, and right and left cranial diagonals, and good intra- and interrater reliability in maximal cranial circumference measurement.